A new approach to computer–aided vibration surveillance of rotating machinery. (4th August 2014) - Qu, Liangsheng; Chen, Yaodong; Liu, Xiong
The necessary hardware and software supports for a high–performance computer–aided vibrational supervision and diagnostic system are discussed. Holospectrum and cascade holospectrum diagrams are introduced. A fuzzy classification method for FFT spectra is proposed to distinguish the abnormal conditions of the rotating machinery. Finally, some practical examples using the above method from oil refineries and power plants are illustrated.